Community and Capital in Entrepreneurship and Economic Growth - Samila, Sampsa; Sorenson, Olav (American Sociological Review, 2017)
We argue that social integration—in the sense of within-community interconnectedness—and venture capital have a complementary relationship in fostering innovation, entrepreneurship, and economic growth. Using panel data on metropolitan areas in the United States from 1993 to 2002, our analyses reveal that racial integration—in the microgeography of residential patterns—moderates the effect of venture capital, with more ethnically-integrated places benefiting more from venture capital. We provide evidence for the underlying mechanisms by demonstrating that communities with higher levels of racial integration foster the discovery of more novel and more valuable inventions and the emergence of more ethnically-diverse entrepreneurial groups.